ESSENTIAL SYSTEMIC HYPERTENSION: GENETICS, CLINICS, EXPERIMENT - А. L. Markel (Российский кардиологический журнал)
The lecture is focused on the exploration of genetic and physiological mechanisms of essential systemic hypertension (ESH). A very brief historic review is provided on the first clinical meanings of the ESH. Then some speculation provided, on its etiology, evolutionary-genetic roots regarding the formation of the main BP regulation systems. More detailed, the data is shown on genetic base of hypertensive conditions and ESH. Also, some discussion given on the monogenic forms of arterial hypertension and polygenic fundamentals of ESH, which is the most among hypertension conditions of human. Modern methods considered for genetic origins of ESH evaluation, and a necessity is underlined for the main etiological factors revealing — as of their interrelation for development of rational treatment and prevention methods against ESH.